1740c Balance of informal workers in latin america: challenges and barriers to access to health and social security. (24th April 2018) - Solar, O; Bernales, P; Gonzalez, MJ; Riesco, A; Vives, A
Abstract : Introduction: Employment and working conditions are recognised as social determinants of health; however, there are limited data on the relationship of informal work and employment conditions with health inequalities. Methods: As part of The Work, Employment, and Health Equity Program was conducted a study to identify available data on informal work and access to health and social security in 12 countries in Latin America. We then measured the magnitude of informality, contextual factors related to informal work, and the characteristics of informal workers and their health. The methodology included Case Studies were oriented to analyse access to health and social security, their employment and working conditions and their relationship to the characteristics of the countries´ economic structure; Focus group Studies collected the primary information based on the informal workers' perception and measured the magnitude of informality, contextual factors related to informal work, and the characteristics of informal workers and their health Result: In Latin America, informal work is higher among women than among men. Analyses showed that health status, access to services and financial protection was poorer among informal compared to formal workers. People work informal economy are higher rate of work among eldest and youngest groups and living in urban and rural. Discussion: Despite limited secondary data on informal work and health in some countries, our results suggest that informal workers are a large and diverse proportion of the working population in Latin America. Employment and working conditions must be studied further to understand the unique risks and drivers of health inequalities in addition to informing effective policies and programs to promote the health of workers worldwide. The lack of evidence on this subject has been detrimental to the development of sound policies addressing access to health by people-WIE and their families.